Co-processing as a tool to improve aqueous dispersibility of cellulose ethers. (2nd November 2015) - Sharma, Payal; Modi, Sameer R.; Bansal, Arvind K.
Abstract: Cellulose ethers are important materials with numerous applications in pharmaceutical industry. They are widely employed as stabilizers and viscosity enhancers for dispersed systems, binders in granulation process and as film formers for tablets. These polymers, however, exhibit challenge during preparation of their aqueous dispersions. Rapid hydration of their surfaces causes formation of a gel that prevents water from reaching the inner core of the particle. Moreover, the surfaces of these particles become sticky, thus leading to agglomeration, eventually reducing their dispersion kinetics. Numerous procedures have been tested to improve dispersibility of cellulose ethers. These include the use of cross-linking agents, alteration in the synthesis process, adjustment of water content of cellulose ether, modification by attaching hydrophobic substituents and co-processing using various excipients. Among these, co-processing has provided the most encouraging results. This review focuses on the molecular mechanisms responsible for the poor dispersibility of cellulose ethers and the role of co-processing technologies in overcoming the challenge. An attempt has been made to highlight various co-processing techniques and specific role of excipients used for co-processing.